2015
DOI: 10.1016/j.jnutbio.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa procyanidins with different degrees of polymerization possess distinct activities in models of colonic inflammation

Abstract: Procyanidins are available in the diet from sources such as cocoa and grapes. Procyanidins are unique in that they are comprised of repeating monomeric units and can exist in various degrees of polymerization. The degree of polymerization plays a role in determining the biological activities of procyanidins. However, generalizations cannot be made regarding the correlation between procyanidin structure and bioactivity, because the size-activity relationship appears to be system-dependent. Our aim was to screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 39 publications
6
44
0
Order By: Relevance
“…The normal phase chromatogram exhibits a large peak with a retention time around 65 min that is comparable to that seen with polymeric (DP 7+) PACs (Fig. 1) [25, 26]. …”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…The normal phase chromatogram exhibits a large peak with a retention time around 65 min that is comparable to that seen with polymeric (DP 7+) PACs (Fig. 1) [25, 26]. …”
Section: Resultsmentioning
confidence: 76%
“…The polyphenolic profile of the CBE was determined by normal-phase HPLC profiling with fluorescence detection and UPLC-MS to quantify the compounds using a modification of our previously reported method [25, 26]. In brief, normal-phase HPLC was performed using an Agilent Technologies 1260 Infinity HPLC equipped with a fluorescence detector (λ ex = 230 nm; λ em = 321 nm).…”
Section: Methodsmentioning
confidence: 99%
“…The fact that polymeric proanthocyanins were found in cocoa extract but not in grape seed extract, could explain this effect, since the anti-inflammatory potential of proanthocyanins with high-degree of polymerization inhibits NF-κB activation and the secretion of eicosanoids and pro-inflammatory cytokines [51]. These results also agree with the activation of IL-4 secretion (an anti-inflammatory cytokine) [52] and the decreased levels on IL-8 (a pro-inflammatory cytokine) [53] by proanthocyanins with a high degree of polymerization.…”
Section: Resultsmentioning
confidence: 89%
“…When permeable support systems such as transwell or Ussing chamber (UCh) are used, alterations in barrier integrity and paracellular permeability of epithelial cell monolayers are evaluated by transepithelial electrical resistance (TEER), an electrophysiological parameter that measures ion conductance across the monolayer, and by the transepithelial transport of molecular markers such as Lucifer yellow (LY) and fluorescently labeled dextrans (FD) [95,96]. Some in vitro studies have associated PACs with increased TEER and decreased transport of permeability markers in the context of barrier dysfunction [77, 78,80]. The expression levels of TJ proteins (claudins, occludins, and ZOs) often correlate, but not always [79], with intestinal permeability and are also considered markers of epithelial integrity.…”
Section: In Vitro Studies Of Barrier Integritymentioning
confidence: 99%
“…The expression levels of TJ proteins (claudins, occludins, and ZOs) often correlate, but not always [79], with intestinal permeability and are also considered markers of epithelial integrity. Bitzer et al [78] found that the dextran sodium sulfate (DSS)-induced loss of barrier function in Caco-2 cells was significantly inhibited by polymeric PACs of cocoa but not by oligomers. Moreover, a higher barrier-protective activity was determined in PACs with DP ≥ 7, which were able to reduce the detrimental effect of DSS in a dose-dependent fashion [78].…”
Section: In Vitro Studies Of Barrier Integritymentioning
confidence: 99%